Catalytic Asymmetric Synthesis of Cyclic Ethers Containing an α‐Tetrasubstituted Stereocenter1. Issue 18 (8th April 2013) - Cox, Nick; Uehling, Mycah R.; Haelsig, Karl T.; Lalic, Gojko
<x xml:space="preserve">Abstract</x> 'Ether' furan or pyran: The exo‐selective cyclization of enantioenriched allenols is accomplished with high chirality transfer using as little as 0.02 mol % of a gold catalyst. The new method is effective in the synthesis of a wide range of enantioenriched cyclic ethers, which are prepared in excellent yields in three steps from readily available propargylic phosphates.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>